MATHEMATICAL LITERACY DEVELOPMENT THROUGH REAL-TIME SOCIOECONOMIC DATA ANALYSIS IN SENIOR HIGH SCHOOLS - Ricky Ekaristy Purwadi; Asep Suhana; R. Apit Rahmat Salamet (INJOSEDU: International Journal of Social and Education, 2026)
Mathematical literacy is an essential competency needed by students to understand, interpret, and use mathematical concepts in various real-life contexts, particularly in facing increasingly complex social and economic dynamics. The development of digital technology and the availability of real-time socioeconomic data open new opportunities in mathematics learning at the senior high school level, particularly in linking abstract concepts to relevant contextual problems. This study aims to systematically examine the development of mathematical literacy through the use of real-time socioeconomic data analysis in mathematics learning in senior high schools. The method used is a literature review by examining relevant scientific articles, proceedings, and research reports, both national and international, published within a certain time frame. The results of the study indicate that the integration of real-time socioeconomic data in mathematics learning can improve conceptual understanding, mathematical modeling skills, critical reasoning, and data-based decision-making skills in students. In addition, this approach also encourages active student engagement, increases the relevance of learning, and strengthens the connection between mathematics and real-world phenomena. However, this study also identifies several challenges, such as teacher readiness, the availability of technological infrastructure, and the need for adaptive and contextual learning designs. This research is expected to provide conceptual contributions to the development of innovative and contextual mathematics learning strategies to improve students' mathematical literacy in the data-driven era.